2007
DOI: 10.1029/2007pa001471
|View full text |Cite
|
Sign up to set email alerts
|

A biogenic origin for anomalous fine‐grained magnetic material at the Paleocene‐Eocene boundary at Wilson Lake, New Jersey

Abstract: [1] The Paleocene-Eocene Thermal Maximum, which occurred $55.5 Ma, was caused by a massive release of carbon, as indicated by an $3% negative carbon isotope excursion recorded in the marine, atmospheric, and terrestrial reservoirs. One suggested source for the carbon, a cometary impactor, is based on the sudden appearance and high concentration of single-domain (SD) magnetite in Paleocene-Eocene (P-E) boundary cores from the North Atlantic continental margin. We evaluate the potential sources of SD magnetite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 55 publications
13
73
0
Order By: Relevance
“…Subsequent studies have confirmed the anomalously high concentrations of SD-like material from the CIE clay from the Atlantic Coastal Plain, making these CIE sections the thickest dominated by SD magnetite recognized thus far in the stratigraphic record (9,10). In these follow-up studies, scanning electron microscopic (SEM) and TEM observations on magnetically extracted materials revealed the presence of chains of magnetite crystals that strongly resembled magnetosomes of magnetotactic bacteria (MTB); this finding led to the conclusion that the SD-like magnetic properties of the CIE clays were predominantly of biogenic origin.…”
mentioning
confidence: 76%
“…Subsequent studies have confirmed the anomalously high concentrations of SD-like material from the CIE clay from the Atlantic Coastal Plain, making these CIE sections the thickest dominated by SD magnetite recognized thus far in the stratigraphic record (9,10). In these follow-up studies, scanning electron microscopic (SEM) and TEM observations on magnetically extracted materials revealed the presence of chains of magnetite crystals that strongly resembled magnetosomes of magnetotactic bacteria (MTB); this finding led to the conclusion that the SD-like magnetic properties of the CIE clays were predominantly of biogenic origin.…”
mentioning
confidence: 76%
“…The highest ratios are exhibited in the shallower cores: M r /M s during the PETM is nearly uniformly $0.40 at Clayton and $0.35 at Ancora (Figure 2), while at more distal Bass River, M r /M s varies within the clay between $0.10 and $0.30 [Kent et al, 2003]. Lippert and Zachos [2007] profile magnetic hysteresis parameters through the Wilson Lake drill core, proximal to Clayton.…”
Section: Geological Settingmentioning
confidence: 96%
“…If biological productivity and organic carbon preservation were constant, the $4 -5 fold increase in sedimentation rate should produce a comparable decrease in organic carbon content. At Wilson Lake, however, organic carbon content predominantly remains $0.3% to $0.4% before, during, and after the CIE [Lippert and Zachos, 2007;Zachos et al, 2006]. Moreover, because particles with high mineral surface area generally preserve organic carbon better than coarser particles [Hedges and Keil, 1995], clay sediments deposited during the CIE should more effectively preserve organic carbon than the underlying and overlying silts.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent studies (7,8) recently demonstrated that the unusual abundance of Ϸ30-to 120-nm-sized magnetite (Fe 3 O 4 ) particles in PETMage sediments from several drill cores from New Jersey (9) was produced by magnetotactic bacteria. Rock magnetic data from similar studies on marine sediments from New Zealand (10) and Egypt* are consistent with the occurrence of magnetofossils at these locales as well.…”
mentioning
confidence: 99%